2012
DOI: 10.1088/1674-1056/21/2/028201
|View full text |Cite
|
Sign up to set email alerts
|

Spinel lithium titanate (Li4Ti5O12) as novel anode material for room-temperature sodium-ion battery

Abstract: This is the first time that a novel anode material, spinel Li 4 Ti 5 O 12 which is well known as a "zero-strain" anode material for lithium storage, has been introduced for sodium-ion battery. The Li 4 Ti 5 O 12 shows an average Na storage voltage of about 1.0 V and a reversible capacity of about 145 mAh/g, thereby making it a promising anode for sodiumion battery. Ex-situ X-ray diffraction (XRD) is used to investigate the structure change in the Na insertion/deinsertion process. Based on this, a possible Na s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 27 publications
3
76
0
Order By: Relevance
“…As can be seen from the ex situ X-ray diffraction (XRD) result in our previous report 32 , several new peaks corresponding to the peaks of Li 4 Ti 5 O 12 but with lower diffraction angles appear during the sodium insertion process; by a rough calculation we found that a new cubic structure with larger lattice parameters (ca. 13% volume expansion compared with Li 4 Ti 5 O 12 ) is formed.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…As can be seen from the ex situ X-ray diffraction (XRD) result in our previous report 32 , several new peaks corresponding to the peaks of Li 4 Ti 5 O 12 but with lower diffraction angles appear during the sodium insertion process; by a rough calculation we found that a new cubic structure with larger lattice parameters (ca. 13% volume expansion compared with Li 4 Ti 5 O 12 ) is formed.…”
supporting
confidence: 50%
“…Inferring from the ex situ XRD results 32 , a new phase sharing the same cubic structure but with a larger lattice parameter emerges after the sodium insertion. Electrochemical measurements show that about three Na ions can be inserted into one formula unit of Li 4 Ti 5 O 12 , whereas elemental analysis of ARTICLE NATURE COMMUNICATIONS | DOI: 10.1038/ncomms2878 the electrolyte and the counter electrode indicates that no lithium is released after cycling.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The LTO is introduced for sodium ion-batteries to extend lifetime and provide fast charging facilities [4]. In order to meet the modern society needs for flexible and durable energy storage devices, another research has conducted to propose a new structure of thin and flexible Li-ion battery design [5]. The goal of proposed design was to reach to high energy density with mechanical flexibility.…”
Section: Related Workmentioning
confidence: 99%
“…Traditional lithium ion batteries with graphite anodes can be damaged, or even explode, due to thermal runaway caused by high internal temperatures or short circuit [18]. However, the lithium titanate battery, a novel lithium-ion battery that uses an alternative anode material (Li 4 Ti 5 O 12 instead of graphite) [19], is proposed to be highly safe, since its internal resistance rises sharply during thermal runaway, thus preventing explosion. Lithium titanate batteries also present more significant advantages, including higher power density and longer life cycles, compared with traditional graphite anode lithium batteries [10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%